2006
DOI: 10.7326/0003-4819-144-11-200606060-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Coffee and Napping on Nighttime Highway Driving

Abstract: Drinking coffee or napping at night statistically significantly reduces driving impairment without altering subsequent sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(91 citation statements)
references
References 33 publications
3
85
1
2
Order By: Relevance
“…However, no detrimental effects on recovery sleep were observed in the Philip et al (2006) study. These authors examined nighttime driving performance between 2.00 and 3.30 a.m. after placebo, 30 min of napping, or 200 mg caffeine.…”
Section: Caffeine and Recovery Sleepcontrasting
confidence: 52%
See 1 more Smart Citation
“…However, no detrimental effects on recovery sleep were observed in the Philip et al (2006) study. These authors examined nighttime driving performance between 2.00 and 3.30 a.m. after placebo, 30 min of napping, or 200 mg caffeine.…”
Section: Caffeine and Recovery Sleepcontrasting
confidence: 52%
“…These authors examined nighttime driving performance between 2.00 and 3.30 a.m. after placebo, 30 min of napping, or 200 mg caffeine. An important difference between the Philip et al (2006) study and studies in which a clear effect of caffeine on recovery sleep was observed might be the length of the sleep deprivation period used. Carrier et al (2009), for example, exposed their participants to 25 h of sleep deprivation, while participants in the Philip et al (2006) study were allowed to go to sleep immediately after the nighttime driving session (i.e., after 3.30 a.m.).…”
Section: Caffeine and Recovery Sleepmentioning
confidence: 85%
“…Following an earlier study by Anund et al (2008), the answers were categorized into four clusters of behaviors: supplementary rest break (breaks other than statutory), in-vehicle alertness-enhancing activity, napping, and caffeine ingestion. Based on what is known about the effectiveness of different SCMs (e.g., Horne et al, 2008;Macchi et al, 2002;Pallesen et al, 2010;Philip et al, 2006;Reyner and Horne, 1998;Sagaspe et al, 2007;Schwarz et al, 2012), the latter two of the clusters were further combined into efficient SCMs outside statutory rest breaks.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…There is also substantial evidence that even short naps (30 minutes or so) provide some benefit, improving performance after both normal and restricted nights of sleep. [36][37][38][39][40][41][42][43] The restorative value of sleep is known to be compromised by higher frequency interruptions (at least every few minutes). Among young adults, experimental sleep fragmentation leads to increased sleepiness and degradation of performance and mood.…”
Section: Managing Fatigue Riskmentioning
confidence: 99%